A Program-Based Comparative Study of Enjoyment of Mathematics Lessons and Career Aspirations of Upper Secondary Students under Math-Science and Math-English Programs According to Their Career Fields in Assumption College, Bangrak, Thailand - Kumar, Shiv; González González, Orlando Rafael (Scholar: Human Sciences, 2021)
This study was conducted on Math-Science and Math-English program students at Assumption College, Bangrak, Thailand, to examine their enjoyment of mathematics lessons, career aspirations and career fields sought, as well as their enjoyment of mathematics lessons according to their career fields. A population sample of 142 upper secondary students enrolled in the English program during the academic year 2018-2019 at the target school, participated in this study. For data collection purposes, two research instruments were used: the Questionnaire on Enjoyment of Mathematics Lessons (QEML) (adaptation of TOSRA, originally developed by Fraser, 1981) and the Career Aspiration Scale-Revised (CAS-R) (Gregor & O’Brien, 2015). Upon data collection, both the QEML (used to determine the participants’ enjoyment of mathematics lessons) and the CAS-R (used to determine the participants’ career aspiration and sought-after career fields) were found to be reliable instruments. In order to test the hypotheses of this study, the collected data were statistically analyzed, performing independent samples t-test and a 6 (career field) ´ 2 (academic program) factorial analysis of variance. It was found that there was a significant difference in the enjoyment of mathematics lessons held by the participants, according to their academic program. However, no significant difference was found in the career aspirations between Math-Science and Math-English program students. The study also revealed that the interaction between the career field and the academic program had no statistically significant effect on the enjoyment of mathematics lessons of the participating students. Based on the research findings, recommendations for teachers, school administrators, students and future researchers are provided.